Predictors of Successful Weaning From Veno-Arterial Extracorporeal Membrane Oxygenation After Coronary Revascularization for Acute Myocardial Infarction Complicated by Cardiac Arrest: A Retrospective Multicenter Study. Issue 6 (June 2019) - Sugiura, Atsushi; Abe, Ryuzo; Nakayama, Takashi; Hattori, Noriyuki; Fujimoto, Yoshihide; Himi, Toshiharu; Sano, Koichi; Oda, Shigeto; Kobayashi, Yoshio
ABSTRACT: Aim: While veno-arterial extracorporeal membrane oxygenation (VA-ECMO) has been utilized to resuscitate and stabilize hemodynamics in patients of acute myocardial infarction (AMI) complicated by cardiac arrest (CA), it is essential to predict the possibility of weaning from ECMO to determine further strategies, including use of ventricular assist device. We aimed to determine predictors of successful weaning from VA-ECMO in the early phase of ECMO treatment. Methods: We identified consecutive patients of AMI complicated by CA treated with VA-ECMO and percutaneous coronary intervention (PCI). Clinical data within 48 h after ECMO initiation were assessed and multiple logistic regression analysis was performed to determine independent predictors of weaning outcome. Results: Fifty-five patients were analyzed. While 28 (51%) patients were successfully weaned from VA-ECMO, 27 (49%) failed to wean. Multivariate analysis identified post-PCI thrombolysis in myocardial infarction (TIMI) flow grade ( P = 0.046), mean arterial pressure (MAP) at 4 h after ECMO initiation ( P = 0.010), and serum lactate at 24 h ( P = 0.015) as independent predictors of successful weaning. Left ventricular ejection fraction (LVEF) at 24 and 48 h was significantly greater in the successful weaning group ( P = 0.014, P = 0.025, respectively). Conclusions: Successful weaning from VA-ECMO was predicted by post-PCI TIMI flow grade, MAP at 4 h, and serum lactate at 24 h after VA-ECMO initiation in patients of AMI complicated by CA. Furthermore, in patients who failed to wean from ECMO, LVEF did not recover within 48 h. In such patients, adjunctive use of other circulatory mechanical devices must be considered.